Strategic Planning, Key Tool for Brand Management in the New Advertising Context - Mayorga-Escalada, Santiago (2016)
New market conditions combined with continuous technological development in Communication, push brands to take decisions in order to ensure viability. This adaptation process makes corporations to rethink new methods of Advertising Communication. Consumers have also changed, they are well informed and discerning buyers, a fact that forces brands to build relevant relationships with their audiences letting brands to develop powerful positioning connections and create added value. These new conditions lead brands to professionalize their management practices, developing comprehensive strategic planning process to manage their brand image building through the marketing mix also called branding.